Innovaciones industriales tempranas, empresarios, mujeres letradas y comerciantes mapuche en la frontera de Concepción y la Araucanía. El Correo del Sur 1849-1865. - Gómez, Yéssica González; Rojas, Carlos del Valle; Córdova, Luis Iván Inostroza (Memoria Americana, 2022)
This article uses the records of the newspaper El Correo del Sur, published in Concepción -a city located in the south of the nascent state of Chile- between 1849 and 1865, to examine perceptions of the historical changes unleashed by the innovations of the industrial revolution, linked with the installation of milling factories, the development of coal mining, the use of steam engines and the publication of newspapers. Particularly it focuses in the point of view of the emergent new social agents, such as businessmen, elite women and salaried workers, also joined by traditional actors as Mapuche merchants around the Araucanía border who remained outside the republican state. These people were reported on in the newspaper as characters which articulated the transition to a global market economy.